The relationship between women earning potential, financial need, household responsibilities and workplace environment towards women work-life conflicts at UiTM Jengka, Pahang / Alia Nadirah Ab Rased - Ab Rased, Alia Nadirah (Faculty of Business and Management, 2019)
The final report project was carried out in order to fulfill the requirement of the Academic Project (ASM662). The study has conducted at the UiTM Jengka, Pahang. There are four main objectives are to identify the relationship between women earning potential and women work-life conflict, to identify the relationship between financial need and women work-life conflict, to identify the relationship between household responsibilities and women work-life conflict and to identify the relationship between workplace environment and women work-life conflict. The number of population of the women lecturers at UiTM Jengka, Pahang is 150. So, the sample sizes are taken referred to the sample size for a given population which is 108 based on Krejcie and Morgan table (1970). The sampling technique used is simple random sampling technique. The data will be analyzed and interpreted using SPSS software. It is hope that from the overall findings, I could discover that employees at UiTM Jengka, Pahang specifically women to have work-life conflict at the office. The employees able to know more about the work-life conflict which is in women earning potential, financial need, household responsibilities and workplace environment. It is hope that the more significant it is toward handling the issues among them